Females Higher Education in Pakistan: An Analysis of Socio-Economic and Cultural Challenges - Mehmood, Sumara; Chong, Li; Hussain, Mehmood (Advances in Social Sciences Research Journal, 2018)
The developed nations around the world pay equal attention to male and female’s higher education, however female’s higher education in developing countries is most neglected sector, and same is true for Pakistan. Though the total enrollment in HEI’s has increased from 0.276 million during 2001-02 to 1.298 million by 2014-15, but still Pakistan’s GER in higher education was just 10% during 2015-16. For instance female’s enrollment has increased from 36.8% to 47.2% by 2014, but the dream of gender equality in higher education is far away. Therefore, the present study is an effort to investigate the socio-economic and cultural challenges to female’s higher education in Pakistan. To support the argument primary data had obtained through a survey feedback of 601 individuals across the country, and results explain that females are facing wide ranging socio-economic and cultural challenges during the attainment of higher education.